Preliminary Pharmacognostic and Phytochemical Screening of Leaves of Cosmostigma racemosum (roxb.) Wight. - Aparna S G; A Shahul Hameed (International Journal of Ayurveda and Pharma Research, 2022)
Pharmacognostic and phytochemical evaluation are necessary for drug authentication and for prediction and confirmation of pharmacological activities of any plant part. Cosmostigma racemosum (Roxb.) Wight, a traditional and folklore drug in Kerala with many reputed usages, locally called as Vaattuvalli, is a shrubby twiner of Apocynaceae family. Leaves are the most used plant part. As no scientific data regarding its standards were available, preliminary pharmacognostic, physico-chemical and phytochemical evaluation of the leaves were done as per the guidelines of Ayurveda Pharmacopoiea of India and WHO. The study revealed that leaves of Cosmostigma racemosum (Roxb.)Wight are simple, opposite, exstipulate, apex caudate, base cordate and with a characteristic chilly odour. Microscopic examination of leaves revealed the presence of characteristic features such as lacticifers, secreting cells, absence of stomata on the upper epidermis, presence of paracytic stomata on the lower epidermis and presence of calcium oxalate crystals especially druse crystals. The preliminary phytochemical evaluation revealed the presence of tannins, alkaloids, steroids, saponins which indicates the wide range of pharmacological activities of the plant. The 13 peaks in the HPTLC profile indicate a wide pharmacological prospect of the leaves. The ICP-MS analysis confirmed that heavy metals like Cd, Cr, Zn, Cu, Pb and As present in the leaves are within permissible limits. Physicochemical parameters such as moisture content, different ash values, volatile oil content, different extractive values, ph, fibre content, and sugar content were also determined. All these findings can serve as standards for assuring the safety, quality and purity of the drug.